2010
DOI: 10.1002/acp.1738
|View full text |Cite
|
Sign up to set email alerts
|

The fading affect bias begins within 12 hours and persists for 3 months

Abstract: Research has shown that the tendency for emotional affect to fade more over time for unpleasant events than for pleasant events, known as the Fading Affect Bias (FAB), increased across 3-month, 9-month and 4.5-year intervals. The current study attempted to determine the temporal locus of the FAB using the data set by Walker et al. as well as two additional data sets. All three data sets showed that the FAB was present after 1 day and persisted for 3 months, even though the affective fading for initially pleasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…In this case unpleasant events were rated as being slightly less intense (M = 6.03) than pleasant events (M = 6.3; x 2 (1) = 32, p<.001) at event occurrence. However, this is not an unusual finding in the FAB literature (Gibbons et al, 2011;Ritchie et al, 2009). In fact, the initial emotional intensity difference demonstrates the robustness of the FAB (as measured by mean fading affect scores): even though pleasant events had more room to fade in emotional intensity between event occurrence and recall, unpleasant events still faded in intensity to a significantly greater extent.…”
Section: Fading Affect Bias Prior To Type Of Disclosure and Listener mentioning
confidence: 68%
See 4 more Smart Citations
“…In this case unpleasant events were rated as being slightly less intense (M = 6.03) than pleasant events (M = 6.3; x 2 (1) = 32, p<.001) at event occurrence. However, this is not an unusual finding in the FAB literature (Gibbons et al, 2011;Ritchie et al, 2009). In fact, the initial emotional intensity difference demonstrates the robustness of the FAB (as measured by mean fading affect scores): even though pleasant events had more room to fade in emotional intensity between event occurrence and recall, unpleasant events still faded in intensity to a significantly greater extent.…”
Section: Fading Affect Bias Prior To Type Of Disclosure and Listener mentioning
confidence: 68%
“…Research has also confirmed the FAB cannot be attributed to differing event age or ease of recall for pleasant versus unpleasant events Skowronski, Gibbons, Vogl et al, 2004;Walker et al, 1997). Importantly, studies also confirm that emotional intensity is usually equivalent for pleasant and unpleasant events at event occurrence, making the temporal locus of the FAB the emotional intensity felt at event recall (Ritchie et al, 2006;; although see Gibbons, Lee & Walker, 2011).…”
Section: Effects Of Social Disclosurementioning
confidence: 92%
See 3 more Smart Citations